Manajemen Perilaku Organisasi Untuk Meningkatkan Kualitas Pendidikan di Era Digital - David Christ Arjo; Erni Murniarti (Yayasan Darussalam Bengkulu, 2026)
Entering the current digital era, education requires changes in how people behave, making it a crucial factor in transforming the way educational institutions operate. This study, conducted using a literature review method from 2020 to 2026, aims to analyze the role of behavioral management in improving the quality of education. The results of this study reveal that the quality of education is strongly influenced by positive attitudes and a passion for learning within individuals, as well as solid teamwork. Transformational leadership plays a crucial role as a guide that creates security for teachers to continue innovating. Meanwhile, a flexible and adaptive organizational culture serves as a moral foundation in facing the changes that occur. Management must be able to overcome objections to change with a humane and data-driven approach. In conclusion, improving the quality of education in the digital era can only be achieved through a combination of the use of advanced technology and the development of responsive and professional organizational behavior.